2021
DOI: 10.3390/nano11040901
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Characterization and Moderate Cytotoxicity of Magnetic Mesoporous Silica Nanocomposite for Drug Delivery of Naproxen

Abstract: In this study, we describe the magnetic and structural properties and cytotoxicity of drug delivery composite (DDC) consisting of hexagonally ordered mesoporous silica, iron oxide magnetic nanoparticles (Fe2O3), and the drug naproxen (Napro). The nonsteroidal anti-inflammatory drug (NSAID) naproxen was adsorbed into the pores of MCM-41 silica after the ultra-small superparamagnetic iron oxide nanoparticles (USPIONs) encapsulation. Our results confirm the suppression of the Brownian relaxation process caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The investigation into the conductive capabilities of magnetic particles has been the focus of research due to its applicability not only in electronic devices but also in the field of medicine and diagnosis [ 5 , 12 ]. Magnetic particles endowed with conductivity have the potential to enhance the detection of low-intensity magnetic fields, providing more accurate values for diagnostic mapping in biomedicine [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation into the conductive capabilities of magnetic particles has been the focus of research due to its applicability not only in electronic devices but also in the field of medicine and diagnosis [ 5 , 12 ]. Magnetic particles endowed with conductivity have the potential to enhance the detection of low-intensity magnetic fields, providing more accurate values for diagnostic mapping in biomedicine [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several examples can be cited, and they are frequently seen in the literature, such as cancer treatment by hyperthermia [ 5 ], tissue engineering and medical implants [ 6 ], and nanomaterial substrates that support stem cell growth [ 7 ]. Another technological advantage that we can gain is by combining nanoparticles with other materials, such as a surfactant [ 3 , 4 , [8] , [9] , [10] , [11] ], which brings more applications, such as drug delivery [ 12 ], selectivity to NP [ 8 , 13 ], substitution for organic contrasts [ [14] , [15] , [16] ], and increases the biocompatibility and stability of the material [ [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…In our recent works 22 , 23 , 28 , 29 we have studied in vitro biocompatibility and cytotoxicity of various mesoporous silica materials, non-modified or surface ligand modified. We did cytotoxicity experiments on the U87 MG and SKBR3 cancer cells using the microscopic techniques, flow-cytometry, MTT assay, apoptosis assay and CAM assay.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this knowledge and great drug delivery potential of MSNs, in our previous works, we have described the different mesoporous silica particles for pH driven drug release 22 , 23 , redox potential driven release 24 , temperature driven drug release 25 or light driven drug release 26 , 27 . In addition to physicochemical-characterisation, we studied biocompatibility and cytotoxicity of the prepared DDS in vitro on the U87 MG and SKBR3 cells using the microscopic techniques, flow-cytometry, MTT assay, apoptosis assay and CAM assay 22 , 23 , 28 , 29 . As a continuation of these works in the present study, we studied the functionality of such systems in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The study of functionalized magnetic nanoparticles (MNPs) has shown tremendous technological advantageous features for biomedical applications [ 6 , 7 , 8 ], such as MRI contrast [ 9 , 10 ] and drug delivery systems [ 11 ], to increase efficiency by releasing a specific drug in a target tissue, without possible damage to healthy tissues [ 5 , 12 , 13 ]. In the presence of a magnetic field, MNPs can be driven to a specific location, increasing the drug concentration [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%